Identifying citrus self-incompatibility genotypes (S-genotypes) and discovering self-compatible mutants - Guanghua Cai; Dan Song; Kang Peng; Jianbing Hu; Peng Chen; Chuanwu Chen; Junli Ye; Zongzhou Xie; Xiuxin Deng; Lijun Chai (Horticulture Advances, 2024)
Abstract Utilizing 32 previously identified S ribonuclease (S-RNase) gene sequences and abundant citrus resources, this study designed specific primers for 10 S-RNase genes. A total of 32 pairs of primers were used to analyze the self-incompatibility genotypes (S-genotypes) of 241 citrus resources, encompassing 105 mandarins, 47 pummelos, 69 oranges, and 20 lemons and citrons. These results provide theoretical guidance for parent selection in production and breeding programs. Among the 215 samples analyzed, two normal S-genotypes were identified, while no S-genotypes were detected in three samples. Notably, 21 samples, primarily citrons, exhibited amplification of only one S-genotype. Additionally, two pummelo samples showed amplification of three S-genotypes each. The integration of S-genotype and selfing phenotype identification revealed five newly discovered self-compatible mutated materials: Changsha ‘Shatian’ pummelo, large-fruited red pummelo, slender leaf ‘Mangshanyegan’, ‘Shatangju’, and W. Murcott. These findings provide valuable resources for investigating the self-compatibility mechanism in citrus.